Science Education for Public and Design of Infrastructure at Rest Area KM 260B Banjaratma - Yerisca Novri Nathania Saragih; Asep Mulyana; Wa Ode Yuznita (Jurnal Penelitian Pendidikan IPA, 2023)
Rest areas on toll roads are an important public infrastructure of the entire freeway construction. Interesting innovations occur on this toll road section in Brebes district, Central Java. The purpose of this study is to describe how design education and digital promotion design at 260B Banjaratma rest area occur. The research method used in this study is descriptive qualitative with an empirical approach, namely with on the spot research. Data was extracted by observation in the field, in addition to data derived from books, journals and other sources compatible with the research theme. The results of the study found that there is public learning about science in the area, namely science about the chemical process of sugar making, architecture, spatial construction, and microeconomics, (2) there is public learning about the history of the area, the physics of materials, namely the construction of bricks that are strong for hundreds of years, and (3) elements of edutourism, namely the combination of public learning with tourism for visitors or toll road users